Sosialisasi Pengolahan Limbah Kotoran Sapi dalam Pembuatan Biogas di Desa Madureso Kabupaten Mojokerto - Julianti Saffana Zahra; Merry Sunaryo; Fadeli Wibisono; Hikmiah , Syahriatul; Nirmala Kaana Taqiyyaa (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2023)
Cow dung is a waste that can interfere with environmental aspects. Constantly increasing volumes without treatment can interfere with human health. This problem is still a challenge for Madureso Village, Mojokerto Regency, East Java. Economic activity is dominated by the agricultural and plantation sectors. About 70% work as farmers or ranchers, but Madureso Village does not have a different cow dung processing system. To overcome this problem, the P2MD team of the Occupational Safety and Health Student Association of Nahdlatul Ulama University Surabaya initiated waste treatment by processing cow manure into biogas and organic fertilizer. Later, the biogas can be an effort by the local community in Madureso Village, to care about environmental hygiene problems and alternative fuels. Therefore, community service activities are carried out through socialization regarding biogas processing or production. The evaluation of the socialization that has been carried out is that most participants understand the importance of cow dung processing and how to utilize the results of this waste treatment. Thus, it is hoped that the community can carry out biogas processing independently and sustainably. Based on the results obtained during the community service activities, it can be seen that the socialization activity was successful because it has increased participants' understanding of biogas. There was an increase of 94% in post-test results where previously only 61% of respondents knew about biogas.